![x=-3](https://img.qammunity.org/2023/formulas/mathematics/college/hpwwzsayzig9ws40tupwhkcnkxbhs4gyhs.png)
1) The way to tackle this expression is to apply the Distributive Property, a.k.a by the acronym FOIL
2) So, we can write down the following development:
![\begin{gathered} (3)/(4)(x-13)=-2(9+x) \\ (3)/(4)x-(39)/(4)=-18-2x \\ (3)/(4)x+2x=-18+(39)/(4) \\ (3)/(4)x+(8)/(4)x=-(72)/(4)+(39)/(4) \\ (11)/(4)x=-(33)/(4) \\ 4*(11)/(4)x=-(33)/(4)*4 \\ 11x=-33 \\ (11x)/(11)=-(33)/(11) \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/l9etp398pvjw832ng7f1k72tuf8ft2j2kg.png)
Note that we have distributed the factors over the parentheses and then we rewrote those whole numbers as fractions.
Thus, the answer is x=-3